(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article examines what euphemism is, as well as opinions about its origin and use. In order for a word to work as a euphemism, its interpretation must remain ambiguous to the listener. They interpret it literally or euphemistically. This article talks about the function of euphemism in speech.